The waning of materialism - Koons, Robert C.; Bealer, George (Oxford : Oxford University Press, 2010)
The case against materialism comprises arguments from conscious experience, from the unity and identity of the person, from intentionality, mental causation, and knowledge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Materialism